The Role of Environmental Protection for the Tourism Industry: A Case of Vietnam regarding Ecotourism - Thoi, Nguyen Thi (The journal of contemporary issues in business and government, 2021)
Environmental protection is an issue of vital importance to tourism, because the environment is not only a condition for tourism activities but also a decisive factor for that tourism attraction. If tourism can be developed thanks to tourism attraction, the environment plays an important role in this development, especially in the trend of sustainable tourism development. In particular, the environmental protection should be seen from the perspective of studying the capacity of the tourist destination so as not to lead to overload, negative impacts, and impacts on the landscape and living environment. The paper results mention some suggestions based on analysing and comparing other research and data. It is necessary to take into consideration regarding ecotourism in order to keep tourism much more sustainable.